Peran Pembiayaan Syariah dalam Mendorong Kinerja Bisnis dan Sertifikasi Halal bagi Pelaku UMKM Kuliner di Kota Makassar - Nachda Alyaditha; Murtiadi Awaluddin; Rahman Ambo Masse; Fathurrahman Fathurrahman; Kamaruddin Arsyad (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This research aims to analyze the role of sharia financing in improving business performance and encouraging the acceleration of halal certification for culinary MSMEs in Makassar. The research is motivated by limited access to sharia financing and low ownership of halal certification which affects business competitiveness. This research uses a qualitative method with a case study approach through interviews, observation and documentation of MSME actors and sharia financial institutions. The research results show that sharia financing used by MSMEs in the form of murabahah financing through Bank Syariah Indonesia is able to increase business capital, production capacity, income and business development. Apart from that, sharia financing also supports the acceleration of halal certification through capital assistance, improving business facilities, and increasing halal awareness of business actors. However, its use still faces obstacles such as low sharia financial literacy, limited information, and financing administration processes and halal certification. This research shows that sharia financing not only functions as an economic instrument, but also as a means of empowering MSMEs in increasing the competitiveness of businesses based on halal principles.